2015
DOI: 10.1007/s12630-015-0480-2
|View full text |Cite
|
Sign up to set email alerts
|

Failure of metyrosine therapy for preoperative management of pheochromocytoma: a case report

Abstract: Purpose Pheochromocytomas (PHEOS) are rare catecholamine-secreting adrenal tumours requiring surgical resection. Preoperative alpha-adrenergic receptor blockade to prevent intraoperative hypertension has traditionally been achieved with phenoxybenzamine. Due to changes in the availability of phenoxybenzamine in Canada, alternate therapies are needed for patients. We report our first experience using metyrosine, a tyrosine hydroxylase inhibitor, for preoperative management in a symptomatic patient with a unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…In a study from Japan by Naruse et al (2018), they have concluded that it was well tolerated and relieved symptoms by reducing excess catecholamine in pheos patients under both preoperative and chronic treatment. Death, failure of treatment and variation in intraoperative blood pressure in metyrosine patients were reported (Thanapaalasingham et al 2015;Naruse et al 2018).…”
Section: Preparation For Surgerymentioning
confidence: 99%
“…In a study from Japan by Naruse et al (2018), they have concluded that it was well tolerated and relieved symptoms by reducing excess catecholamine in pheos patients under both preoperative and chronic treatment. Death, failure of treatment and variation in intraoperative blood pressure in metyrosine patients were reported (Thanapaalasingham et al 2015;Naruse et al 2018).…”
Section: Preparation For Surgerymentioning
confidence: 99%
“…Although Butz et al reported that patients treated with metyrosine and pheoxybenzamine had wider range of intraoperative blood pressure variations than phenoxybenzamine-only patients ( 47 ), it has been reported by most studies that the combination of metyrosine and α-AR antagonists lead to better blood pressure control, decreased intraoperative blood loss, and reduced volume replacement during operation compared with the classical method of monotherapy of α-AR blockade ( 45 , 46 , 48 , 49 ). In a case report of a patient with PPGL, the administration of metyrosine alone was unable to satisfactorily control intraoperative blood pressure ( 50 ), which was probably due to the incomplete depletion of CA stores no matter what dose used. Therefore, metyrosine is always used in combination with α-AR antagonists in patients with serious symptoms which cannot be well controlled by other medications, such as those with biochemically active tumors or extensive metastatic tumors ( 8 , 45 ).…”
Section: Ca Synthesis Inhibitormentioning
confidence: 99%
“…The initial oral dose is usually 250 mg 3 times a day, which may gradually be increased to a maximum daily dose of 4 g. In general, metyrosine is prescribed in combination with an α-adrenergic receptor blocker, in particular phenoxybenzamine [54][55][56]. A few case reports suggested that monotherapy with metyrosine is less effective (57,58). Similar to phenoxybenzamine, metyrosine is expensive and has a limited availability in several countries.…”
Section: Alternatives To α-Adrenergic Receptor Blockersmentioning
confidence: 99%